Prospects of the EU’s Common Foreign and Security Policy and Russia’s Disinformation Campaign in the South Caucasus - Nino Machurishvili (Studia Europejskie, 2021)
This paper aims to provide an empirical analysis of EU policy towards the South Caucasus in the framework of the CFSP and CSDP along with perspectives of further development, taking in to consideration Russia’s military and ideological intervention in this region, and to address the issue of the EU’s role in shaping Common European Security. Methodologically, the research is based on qualitative techniques of analysis, key assumptions are raised through a comprehensive review of existing studies/primary sources and, more specifi cally, presents a case study of August 2008’s Georgia–Russia military confrontation and creeping occupation. The comprehensive review continues with Russia’s disinformation campaign and series of anti-government protests in Georgia (after the so-called “Gavrilov’s Night”), testing several theoretical explanations such as the democratic peace theory and the Europeanization Confl ict concept concerning the EU’s confl ict resolution instruments’ evaluation and offensive realism to explain Russia’s involvement/intervention in South Caucasus territorial confl icts. As for its structure, the paper includes an introduction, with two important stages of model building – conceptualization and operationalization, an interpretation part – an overview of EU Foreign and Security Policy instruments, relationships with other global/regional actors, confl icts in the South Caucasus, specifi cally the, Georgia case, and, finally, a summarizing part, where key fi ndings are highlighted.